Faith and Morality Within Sufi Texts:: A Note on the Traces of Sufism And Its Textual Tradition In Indonesia - El, Joseph (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2025)
Sufism cannot be separated from the tradition of texts; it is based on the inspiration of Divine Revelation, infused with faith (tawhid), and experienced in practice. This practice is the ‘path of purity and simplicity’ (fuqara, faqir) aimed at uniting with God. Sufism is taught by the Sufis, who are “the chosen ones of God,” according to Reynold A. Nicholson in The Mystics of Islam. Alternatively, according to the author of al-Luma’, as quoted by Nicholson, this term refers to the prophets, who are chosen for their purity, inspirational knowledge, and commitment to carrying out God’s mission. This paper is a textual analysis of existing Sufi works, combined with early Islamic traditions in Indonesia regarding faith and morality. The author employs historical and hermeneutic approaches to understand the traces of Sufism in Indonesia, as well as the mystical speculation and morality that have been essential spirits in the spread of Islam.